Sin puerto para el sueño americano. Políticas de exclusión, inmigración y tracoma en Argentina (1908-1930) - María Silvia Di Liscia; Melisa Fernández Marrón (Nuevo mundo - Mundos Nuevos, 2009)
This paper studies trachoma, an ocular pathology that may cause blindness, in the context of the migratory politics developed in the Argentinean Republic. The detection of the granular conjunctivitis was a reason for rejection from the 1908 until the mid-1940s, despite its decrease started one decade before. The disease was also presented as an argument to prevent the entrance of groups of Russian, Polish (Jewish) and Syrian-Lebanese, amongst others. Our aim is to examine the practice used by the agencies that established that system of exclusion, such as the National Department of Migrations and the National Department of Hygiene, based on a regulation which was related to processes of discrimination and xenophobia. Additionally, this article will analyze the strategies elaborated by individuals in order to resist violence, in a country in which the advertised modernity called for the massive entrance of immigrant population.